2003
DOI: 10.1046/j.1442-2050.2003.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral immune tolerance to tumor specific antigens may confer growth advantage to esophageal and gastric cancers*

Abstract: Oral administration of antigens induces antigen-specific systemic immune tolerance (Oral Tolerance). We postulate that the poorer prognosis of foregut cancers might, in part be explained by the systemic immune tolerizing effect of tumor specific antigens shed into and processed by the gut immune system thus conferring a growth advantage specific to individual cancers. Immunocompetent Balb/c mice were fed by gavage, either tumor tissue (JBS/CarB) in phosphate buffered saline (PBS) or PBS alone, daily for 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In animal models, the presence of numerous maternal cells or soluble antigens in breast milk could induce tolerance to maternal cells (7,8,13), while ingestion of tumor fragments could give the tumor cells a growth advantage (10)(11)(12). These results suggest that breast milk containing maternal leukemic cells, as well as normal cells, might facilitate tolerance to and promote growth of maternal leukemic cells transmitted to the infant during pregnancy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In animal models, the presence of numerous maternal cells or soluble antigens in breast milk could induce tolerance to maternal cells (7,8,13), while ingestion of tumor fragments could give the tumor cells a growth advantage (10)(11)(12). These results suggest that breast milk containing maternal leukemic cells, as well as normal cells, might facilitate tolerance to and promote growth of maternal leukemic cells transmitted to the infant during pregnancy.…”
Section: Discussionmentioning
confidence: 77%
“…Breast milk contains a number of maternal antigens and leukocytes. Another report in mice showed that oral feeding of tumor fragments could confer a growth advantage on, and induce immune tolerance to, tumor cells (10)(11)(12). These findings suggest that breast feeding after delivery could promote a survival advantage for and tolerance to maternal BCR-ABL-positive cells, in the event of their transmission to the infant.…”
Section: Introductionmentioning
confidence: 91%
“…It is likely that tumour Ags derived from tumour tissue shed into the intestine by foregut cancers would be processed by the gut associated lymphoid tissues (GALT), predominantly found in the proximal gastrointestinal tract, in a way reminiscent of Ags ingested by the mucosal immune system, thus creating a tumour Ag specific immune tolerance. We previously reported that orally administered fresh tumour tissue induced a tumour Ag specific non-cross-reactive immune tolerance with a consequent growth advantage for the cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…18 JBS is a negative variant for the large T antigen and was derived from the simian virus 40 (SV40)-transformed 3T3 cell line in our laboratory by Dr John Barrett. 19 The SV40 3T3 cell line is tumorigenic only in immunocompromised mice, for example, MF1 athymic nude mice, and not in the immunocompetent syngeneic Balb/C animal. The JBS cell line was developed from a tumor that occurred spontaneously in one of a panel of Balb/C mice that were inoculated with SV403T3 cells in doses equivalent to those found to be tumorigenic in the athymic mouse.…”
Section: Cell Tissue Culturementioning
confidence: 99%
“…This tumor grows in immunocompetent Balb/C at the same rate as in athymic nude mice. 19 Vaccination strategies, using a diversity of approaches, schedules and cell treatments, failed to protect Balb/C mice from subsequent tumorigenic JBS challenges (Table 1). Thus, this cell is considered weakly or non-immunogenic.…”
Section: Cell Tissue Culturementioning
confidence: 99%